Identifying risk factors for pregnancy and lactation-associated osteoporosis: insights from an Italian survey in PLAO patients and controls - Grassi, Giorgia; Zampogna, Marta; Atlasova, Anna; Rondinella, Sara; Ghielmetti, Alberto; Siracusano, Giordana; Chiodini, Iacopo; Mantovani, Giovanna; Eller-Vainicher, Cristina (Frontiers in Endocrinology, 2025)
BackgroundPregnancy and lactation-associated osteoporosis (PLAO) is characterized by fragility fractures during late pregnancy and postpartum period. The risk factors for PLAO are largely unknown. This study aims to identify the risk factors for PLAO, related and unrelated to pregnancy.Patients and methodsA questionnaire on clinical history, lifestyle factors, nutritional habits, and pregnancy-related characteristics was administered to 155 women with PLAO and 182 women without PLAO.ResultsWomen with PLAO were older (32.9 ± 4.7 years), showed a higher prevalence of BMI <18.5 Kg/m2 (23.6%), eating disorders (11.6%), amenorrhea (7.1%), chronic diseases associated with bone fragility (11.7%), calcium-intake <500 mg/day (66.9%), previous fragility fractures (18.7%), blue sclerae (5.2%) and family history of vertebral/femoral FXs (21.0%) than women without PLAO (31.6 ± 5.4 years, 13.8%, 5.5%, 2.2%, 2.6%, 50.8%, 6.0%, 0.5%, 11.0%, p<0.05 for all comparisons). The risk of PLAO was associated with pre-pregnancy fragility fractures (odds ratio, OR 2.7, 95% Confidence Interval, CI, 1.199-6.036, p=0.016), chronic diseases (OR 5.8 95% CI, 1.919-17.562, p=0.002), age at pregnancy (OR 1.1, 95% CI, 1.005-1.109, p=0.030), BMI<18.5 Kg/m2 (OR 2.0, 95% CI, 1.042-3.902, p=0.037) and calcium-intake <500 mg/day (OR 2.5 95% CI, 1.485-4.166, p=0.01). During pregnancy, PLAO women showed a higher prevalence of insufficient weight gain (49.0%), calcium-intake <500 mg/day (67.1%), history of bed rest (21.9%) and use of low-molecular-weight heparin (LMWH, 25.2%). An increased risk of PLAO was associated with calcium intake <500 mg/day during pregnancy (OR 1.5, 95% CI, 1.047-2.141, p=0.027), insufficient weight gain (OR 1.8, 95% CI, 1.109-3.003 p=0.018) and LMWH use (OR 2.0, 95% CI, 1.124-3.682, p=0.019).ConclusionsPLAO, a condition with relevant impact on women’s health, is associated with BMI <18.5, low calcium intake, age at pregnancy, previous fragility fractures and the presence of chronic diseases before pregnancy and with insufficient weight gain, LMWH use and low calcium intake during pregnancy.